2018
DOI: 10.3389/fneur.2018.00928
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Thrombectomy for Tandem Occlusions of the Internal Carotid Artery—Results of a Conservative Approach for the Extracranial Lesion

Abstract: Background: Mechanical thrombectomy (MT) is of clinical benefit for patients with extracranial-intracranial tandem lesions of anterior circulation. However, the optimal approach to the cervical lesion of the internal carotid artery (ICA) during MT has yet to be established. Data on a conservative approach for the proximal lesion during the acute phase are scarce.Methods: A retrospective study on an institutional, prospective database was conducted. We included patients with anterior circulation stroke presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Despite the encouraging results of the abovementioned studies demonstrating high successful reperfusion rate and good outcome with carotid artery stenting, the need of antithrombotic agents in the acute phase makes it a less appealing approach prompting some experts to recommend alternative approaches such as MT alone or angioplasty without acute stenting ( 16 ). Two retrospective studies demonstrated a high successful reperfusion rate and good outcome with angioplasty or MT alone ( 17 19 ); however, these studies suffered a small sample size. With angioplasty or MT alone approach, antithrombotic agents are often not required; therefore, the risk of hemorrhagic transformation is of lesser concern.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the encouraging results of the abovementioned studies demonstrating high successful reperfusion rate and good outcome with carotid artery stenting, the need of antithrombotic agents in the acute phase makes it a less appealing approach prompting some experts to recommend alternative approaches such as MT alone or angioplasty without acute stenting ( 16 ). Two retrospective studies demonstrated a high successful reperfusion rate and good outcome with angioplasty or MT alone ( 17 19 ); however, these studies suffered a small sample size. With angioplasty or MT alone approach, antithrombotic agents are often not required; therefore, the risk of hemorrhagic transformation is of lesser concern.…”
Section: Discussionmentioning
confidence: 99%
“…Actually no deleterious effect of carotid stenting has been already proved ( 19 ). To date, as Blassiau et al said, choice of strategy “may vary between institution and physicians and adapts as a result of personal experience” ( 17 ), though the absence of consensus. This debate highlights the need of a randomized controlled trial for tandem lesions population.…”
Section: Discussionmentioning
confidence: 99%
“…67 Even if one adopts a conservative strategy for the management of tandem occlusion, angioplasty or stenting may be necessary in up to 31% of cases, simply to provide access to the intracranial lesion. 68 Those that prefer to avoid stenting advocate angioplasty only to provide access to the intracranial vasculature for thrombectomy. They point to the single-center studies that suggest high in-stent thrombosis and intracranial hemorrhage rates, which may be due to the antithrombotic medications used in stenting.…”
Section: Carotid Revascularization During Thrombectomy For Acute Strokementioning
confidence: 99%
“…A favorable clinical outcome (mRS 2) was achieved in 15/35 patients (45.7%) and was associated with higher baseline ASPECTS (OR: 1.62, 95% CI: 1.08-2.45, p ¼ 0.002) and successful recanalization (OR: 9.39, 95% CI: 1.92-45.80, p ¼ 0.0005). 46 Labeyrie et al reported 6 approaches to manage the cervical occlusion in 49 patients with TO (14% of MT): medical treatment alone in 16/64 (25%), stenting/angioplasty in 16/64 (25%), occlusion with coils in 12/64 (19%), angioplasty alone in 9/64 (14%), stent retriever in 8/64 (12%), and/ or thromboaspiration in 3/64 (5%). Early ipsilateral embolic recurrence occurred in 9/64 (14%).…”
Section: Does Coil Occlusion or Staged Revascularization Of The Carotmentioning
confidence: 99%